1999
DOI: 10.1126/science.286.5444.1568
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Conserved Receptor-Binding Site on the Fiber Proteins of CAR-Recognizing Adenoviridae

Abstract: The human adenovirus serotype 5 (Ad5) is used widely for applications in human gene therapy. Cellular attachment of Ad5 is mediated by binding of the carboxyl-terminal knob of its fiber coat protein to the Coxsackie adenovirus receptor (CAR) protein. However, Ad5 binding to CAR hampers the development of adenovirus vectors capable of specifically targeting (diseased) tissues or organs. Through sequence analysis and mutagenesis, a conserved receptor-binding region was identified on the side of three divergent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
268
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(283 citation statements)
references
References 22 publications
13
268
0
2
Order By: Relevance
“…As this site is located on the side of the knob monomer, these findings imply that the trimeric knob could bind to three CAR molecules independently. 18 Bewley et al, 19 by analyzing the crystal structure of the CAR-recognizing Ad12 fiber knob complexed with the D1 domain of the CAR protein, confirmed that the AB loop of the fiber plays an essential role in the interaction with the cellular receptor. Another group also confirmed, by surface plasmon resonance and Gene Therapy cell-binding competition experiments with recombinant mutated Ad fibers, that residues located in the AB and the DE loops and in ␤-strand E and F are directly or indirectly in contact with the cellular receptor.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As this site is located on the side of the knob monomer, these findings imply that the trimeric knob could bind to three CAR molecules independently. 18 Bewley et al, 19 by analyzing the crystal structure of the CAR-recognizing Ad12 fiber knob complexed with the D1 domain of the CAR protein, confirmed that the AB loop of the fiber plays an essential role in the interaction with the cellular receptor. Another group also confirmed, by surface plasmon resonance and Gene Therapy cell-binding competition experiments with recombinant mutated Ad fibers, that residues located in the AB and the DE loops and in ␤-strand E and F are directly or indirectly in contact with the cellular receptor.…”
Section: Introductionmentioning
confidence: 96%
“…15,16 Only recently, through sequence analysis and mutagenesis of the knob domain of the Ad5, has a conserved receptor-binding region been identified. [17][18][19][20][21] These authors demonstrated that the CARbinding site consists of residues from the AB loop, the B ␤-sheet and the DE loop, while the FG loop seems to play an indirect role in binding CAR. As this site is located on the side of the knob monomer, these findings imply that the trimeric knob could bind to three CAR molecules independently.…”
Section: Introductionmentioning
confidence: 99%
“…5,[12][13][14] When an adenovirus particle enters a target cell, two types of receptor-mediated process are involved. First, the fiber knob of the adenovirus capsid binds to the attachment receptor on the cell surface, such as a Coxsackie B and adenovirus receptor (CAR) [15][16][17][18] and a MHC class I ␣2 domain. 19 The CAR has been reported as a 46 kDa transmembrane protein and hCAR cDNA and LacZ gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that the expression of CAR is frequently suppressed in various types of cells, including tumor cells and in primary tumors [4,5], resulting in resistance to adenovirus infection [6][7][8]. Nevertheless, various studies have shown that adenovectors with modified capsid proteins, such as additions of polylysine or RGD sequence to fibers, can effectively infect cells with defective CAR expression [9][10][11]. Thus, modified adenovectors with increased transduction ability or targeting capacity may be useful for various gene transfer or gene therapy studies or clinical applications.…”
mentioning
confidence: 99%